Key-Deduplication With Enhanced Security Using Identity Based Technique - Rani Vellanki, Dr.S.Jessica Saritha (International Journal of Advanced Science and Technology, 2020)
Cloud computing enables new business models and cost effective resource usage. In Cloud Computing Technology Data Storing and Data Sharing plays a major role. In Data Storing we face a main problem of Data deduplication. Various traditional deduplication systems are introduced for elimination of replicate check besides the data itself, but existing techniques are not able to decode compressed files. The proposed architecture provides duplicate check procedures to reduce minimal overhead compared to normal operations. The data stored in cloud will be in compressed format the paper introduces decoding data compression techniques for eliminating duplicate copies of repeating data, through this cloud storage space and upload and download bandwidths can be reduced. The work also presents various new deduplication constructions supporting authorized duplicate check in hybrid cloud architecture. Security analysis exhibit that our scheme is protected in terms of the description particular in the projected security model. The work realize a prototype of proposed approved duplicate check scheme and carry out tested experiments by means of the prototype. We show that our planned authorized replacement check scheme incurs negligible transparency evaluate to normal operations for elimination of duplicate data from clouds.